Conceptual design of 3D printed composite side mirror base using hybrid method - Ab Hamid, Muhammad Khairul Azmir (2024)
The research work presents the stages of producing a conceptual design of a side mirror base that is optimum in shape and utilizes an ideal amount of natural fiber composite, an environmentally friendly material that has the potential to substitute the existing plastic material that is harmful to the environment. To determine the best among five natural fiber composites which are PLA + wood, PLA + coconut, PLA + bamboo, PLA + silk & PETG + wood, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method was used. The material properties from previous research and static simulation results of the created 3D car side mirror base using SolidWorks software were used as the set criteria for the TOPSIS method. Next, The 3D model undergoes the topology optimization simulation using SolidWorks software to obtain the best percentage of material removal and the finalized created model was verified through a static simulation study to ensure the part will not fail. The finalized design was fabricated using the previously selected material through the Fused Deposition Modelling (FDM) method where the finalized model went through processes such as file conversion from CAD file to STL file, slicing, and adjustment of printing parameters before the final model was printed to obtain the end product. The physical form of the conceptual design was weighed to compute the weight reduction obtained when compared to the unoptimized model. Among the five studied natural fiber composites, the TOPSIS method analyzed PLA + wood as the best material for the optimized side mirror base with a 0.9375 performance score. The topology optimization simulation study identified that the best percentage of material removal is 20% and the finalized model was created based on this simulation result. The optimized model weighed at 68.572g and was 11.235g or about 16.38% lighter than the unoptimized model. The TOPSIS method is a useful tool to make decisions involving multiple criteria while topology optimization is a great strategy to produce optimum design. Even if the result of topology optimization comes in complex geometries, the advancement of additive manufacturing such as FDM 3D printing can be utilized to fabricate the end product. The end product of this study is ready to be produced in either small or large scale as the environmentally friendly after-market substitution part to have a significant impact towards world sustainability.